SIGNIFICANCE OF IMMUNOHISTOCHEMISTRY IN ACCURATE CHARACTERIZATION OF MALIGNANT TUMORS - Ahmed, Zubair; Azad, Najamul Sahar; Bhurgari, Yasmeen; Ahmed, Rashida; Kayani, Naila; Pervez, Shahid; Hasan, Sheema (Journal of Ayub Medical College Abbottabad, 2006)
Background: To determine in a large series of surgical biopsies the role and significance of immunohistochemistry in the adequate and accurate characterization of malignant tumors. Methods: A retrospective study of 20,000 consecutive surgical biopsies reported in the Section of Histopathology, AKU in 2003. Data was obtained by retrieving the filed surgical biopsy reports in the section. Results and Conclusions: Out of the 20,000 biopsies, 6534 (32.67%) were neoplastic. 4726 neoplasms (72.33%) were malignant, and 1808 (27.67%) were benign. Immunohistochemistry was performed on 29.49% of malignant tumors, and 4.97% of benign tumors. Immunos were performed on only 2.82% of routine squamous cell carcinomas and adenocarcinomas of various organs, and in only 1.9% of infiltrating breast carcinomas, the commonest malignant tumors in females. In contrast, immunos were performed on 97.12% of non-Hodgkin’s lymphomas, 97.94% of Hodgkin’s lymphomas, 98.09% of malignant spindle cell neoplasms, 87.96% of small round blue cell tumors of childhood, 87.30% of neuroendocrine neoplasms, and 84.37% cases of malignant melanomas. In addition, immunos were performed on all cases of malignant undifferentiated neoplasms and were able to resolve the issue in over 89% of such cases. Immunos were also performed on 54.74% of metastatic tumors. Lymph nodes were the commonest organs on which immunos were performed i.e. 96.50% of lymph node tumors, followed by CNS and renal neoplasms with 33.01% and 25.92% respectively. Key Words: Malignant tumours, Karachi, Immunochemistry